The Broadband Cost Reduction Directive: A legal primer in cross-sector regulation of infrastructures. Issue 1 (March 2021) - Ducuing, Charlotte
Infrastructures have mostly developed and have also been regulated in silo, especially in the liberalization phase. As economic, societal and technological patterns toward convergence of infrastructure sectors can now be observed, how to regulate such phenomena obviously raises many questions. In this context, the cross-sector regulation laid down by the Directive 2014/61/EU on measures to reduce the cost of deploying high-speed electronic communications networks constitutes an interesting legal primer in EU law, although little discussed. Six years after the adoption of the Directive, the present paper aims to draw lessons from it, from its transposition and from the related dispute-settlement practice in the Member States, with the perspective of cross-sector regulation. What type of cross-sector regulation does the Directive bring about? What are the factors having an influence on the (im)balance between the sectors and/or sectoral regulations? It seems all the more necessary that the newly appointed European Commission ("EC") announced its willingness to revise the Directive within the next 5 years. The study of the BCR Directive may also contribute to inform how to regulate the phenomenon of increasing convergence between network industries. The paper refers to "cross-sector regulation" as, broadly, a type of regulation where several sectors, traditionally subject to specific regulations, are brought together, irrespective of the mode of interaction between them. Particularly, "cross-sector regulation" does not assume that the sectors and/or the sectoral regulations would be placed on an equal footing.